In-silico study for African plants with possible beta-cell regeneration effect through inhibition of DYRK1A (Sciences of Phytochemistry, 2022)
The continuous destruction of normal insulin-producing pancreatic beta-cells is a contributing factor in all common forms of diabetes, due to insufficient production of insulin, especially in type 1 diabetes. There are attempts at beta-cells transplantation, but the cost and availability of donors pose a great challenge to the process. Dual-Specificity Tyrosine Phosphorylation-Regulated Kinase A (DYRK1A) plays a crucial role in beta-cells destruction. Our research targets to identify plants that can be utilized as a possible alternative approach to beta-cell replacement through a pharmacologically induced regeneration of new beta-cells in-silico. The 3D structure DYRK1A and 6511 phytochemicals were obtained from the Protein Data Bank and the African Natural Products Database respectively. They were duly prepared for molecular docking simulations (MDS). MDS was implemented, after validation of docking protocols, in AutoDock-Vina®, with virtual screening scripts. Phytocompounds with good binding affinities for DYRK1A were selected as frontrunners. The compounds were screened for toxicity, Lipinski’s rule confirmation with Data Warrior software followed by kinase inhibitory bioactivity prediction with the Molinspiration Chemoinformatics web tool. Twelve phytocompounds were found to be predictably highly active in-silico against DYRK1A with good drug-like property based on Lipinski’s rule, non-mutagenic, non-tumorigenic, no reproductive effect, and non-irritant, with high predicted bioactivity. In-silico active phytocompounds against DYRK1A with their plant sources and physicochemical parameters were identified. Further studies will be carried out in-vitro and in-vivo to validate the results of this study using plants containing the identified phytocompounds.